A comparative study of experimental flow boiling heat transfer and pressure drop characteristics in porous-wall microchannel heat sink. (December 2018) - Jia, Y.T.; Xia, G.D.; Zong, L.X.; Ma, D.D.; Tang, Y.X.
Highlights: The flow boiling experiment are conducted in porous-wall (PW) microchannels. The effect of mass flux, heat flux and vapor quality on microchannels are studied. PW microchannels reduce the wall superheat for ONB and improve the CHF. PW microchannels exhibit obvious heat transfer enhancement with pressure drop reduction. The uniformity and stability of wall temperature are analyzed in PW microchannels. Abstract: In this work, we proposed a porous-wall (PW) microchannel heat sink, in which micro pin fin arrays were fabricated on sidewalls of rectangular microchannels by MEMS (Microelectrical Mechanical System) technique. High speed flow visualizations were performed simultaneously with heat transfer and pressure drop measurements to investigate the flow boiling characteristics of PW microchannel heat sink. Conventional rectangular (Rec) microchannel heat sink was also explored together as a comparison. Experiments were carried out with pure acetone liquid at inlet temperature of 30 °C, mass flux from 255 kg/(m 2 ·s) to 843 kg/(m 2 ·s), heat flux from 4 W/cm 2 to 110 W/cm 2 and the maximum vapor quality at the outlet of the channel was 0.88. Experimental results demonstrated that the PW microchannels reduce wall superheat of onset of nucleate boiling (ONB) and improve critical heat flux (CHF) compared to the Rec microchannels. Moreover, the PW microchannels show significant heat transfer enhancement, pressure drop reduction and mitigation of two-phase flow instability. The porous walls provide numerous nucleation sites and the intensive pin fins arrangements introduce significant wicking effect to maintain the liquid rewetting, which contribute to the above notable flow boiling enhancement.